Effects of climate and land-use change on species abundance in a Central European bird community - Lemoine, Nicole (Conservation biology : the journal of the Society for Conservation Biology, 2007)
Although it is known that changes in land use and climate have an impact on ecological communities, it is unclear which of these factors is currently most important. We sought to determine the influence of land-use and climate alteration on changes in the abundance of Central European birds. We examined the impact of these factors by contrasting abundance changes of birds of different breeding habitat, latitudinal distribution, and migratory behavior. We examined data from the semiquantitative Breeding Bird Atlas of Lake Constance, which borders Germany, Switzerland, and Austria. Changes in the regional abundance of the 159 coexisting bird species from 1980-1981 to 2000-2002 were influenced by all three factors. Farmland birds, species with northerly ranges, and long-distance migrants declined, and wetland birds and species with southerly ranges increased in abundance. A separate analysis of the two decades between 1980-1981 and 1990-1992 and between 1990-1992 and 2000-2002 showed that the impact of climate change increased significantly over time. Latitudinal distribution was not significant in the first decade and became the most significant predictor of abundance changes in the second decade. Although the spatial scale and temporal resolution of our study is limited, this is the first study that suggests that climate change has overtaken land-use modification in determining population trends of Central European birds